Identification of PET radiometabolites by cytochrome P450, UHPLC/Q-ToF-MS and fast radio-LC: applied to the PET radioligands [11C]flumazenil, [18F]FE-PE2I, and [11C]PBR28 - Amini, Nahid; Nakao, Ryuji; Schou, Magnus; Halldin, Christer (Analytical and bioanalytical chemistry, 2013)
A general method is presented for the identification of radiometabolites in plasma of human and monkey subjects after administration of positron emission tomography (PET) radioligands. The radiometabolites are first produced in vitro, using liver microsomes, subsequently separated using fast radio-liquid chromatography (radio-LC), and individually collected and identified by ultra high-performance liquid chromatography/quadrupole-time of flight-mass spectrometry in MS and MS E mode. Fast radio-LC provided superior resolution compared to conventional radio-LC, resulting in separation of a greater number of metabolites. The radiometabolites produced in vivo are then compared to and identified based on the in vitro results. This approach was applied to three PET radioligands, [ 11 C]flumazenil, [ 18 F]FE-PE2I, and [ 11 C]PBR28, resulting in the identification of five, two, and one radiometabolites, respectively. This procedure can easily be adopted to identify the radiometabolites produced in vivo from a variety of PET radioligands.